Requirements Engineering untuk Pengembangan Aplikasi Pemesanan Hotel - Setiawan, Anjar (JNANALOKA, 2025)
This research describes a Requirements Engineering approach focused on stakeholder development in the context of a hotel booking platform. By looking at various stakeholders such as hotels, customers, catering service providers, photographers, and cosmetologists, this research aims to detail the unique needs of each party involved. Stakeholder identification is the first step, followed by an in-depth analysis of the needs of each stakeholder. The main focus includes platform functionality, payment integration, order management, and stakeholder interaction. Data security, privacy, thorough testing, and long-term maintenance planning ensure successful implementation. The results of this research can provide practical guidance for developers in designing a hotel booking platform that meets room reservation standards and integrates additional services optimally, meeting the needs and expectations of each stakeholder involved.